FAKTOR-FAKTOR YANG MEMEPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK PADA UMKM DI KOTA METRO - Nedi Hendri (Akuisisi: Jurnal Akuntansi, 2016)
The Compliance of SME in paying taxes will give a good impact in the creation of new tax sources which is will increase state revenues. However, if the factors affecting SMEs Actors Compliance is negative, then the Taxpayer Compliance will tend to rise and provide a good influence for the state revenue.The purpose of this study was to determine the effect of the Knowledge Taxpayer, Taxation Sanction, Confidence, and awareness of the  Taxpayer Compliance.The research methods used in this research was the analysis of the path (path diagram). The result of the research shows that, the confidence level has no effect on tax compliance in paying taxes. While the knowledge of the taxpayer, tax penalties, and awareness of the taxpayers effect on tax compliance in paying taxes. Keyword: Knowledge of Taxpayer, Taxation Sanction, Faith, Awareness Taxpayers and Taxpayer Compliance.